2012
DOI: 10.1128/aem.00532-12
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Inactivation of Human Norovirus Virus-Like Particles Provides Evidence that the Capsid of Human Norovirus Is Highly Pressure Resistant

Abstract: Human norovirus (NoV) is the leading cause of nonbacterial acute gastroenteritis epidemics worldwide. High-pressure processing (HPP) has been considered a promising nonthermal processing technology to inactivate food-and waterborne viral pathogens. Due to the lack of an effective cell culture method for human NoV, the effectiveness of HPP in inactivating human NoV remains poorly understood. In this study, we evaluated the effectiveness of HPP in disrupting the capsid of human NoV based on the structural and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 38 publications
(93 reference statements)
4
37
0
Order By: Relevance
“…As shown in Fig. 3, and consistent with data described previously (20), two protein bands, with molecular masses of ϳ60 and ϳ50 kDa, corresponding to full-length VP1 and the cleaved form of VP1 (cVP1), respectively, were detected in VLPs. Exposure to stainless steel surfaces resulted in virtually no reduction in the HuNoV VP1 band intensity, regardless of time (Fig.…”
Section: Resultssupporting
confidence: 74%
“…As shown in Fig. 3, and consistent with data described previously (20), two protein bands, with molecular masses of ϳ60 and ϳ50 kDa, corresponding to full-length VP1 and the cleaved form of VP1 (cVP1), respectively, were detected in VLPs. Exposure to stainless steel surfaces resulted in virtually no reduction in the HuNoV VP1 band intensity, regardless of time (Fig.…”
Section: Resultssupporting
confidence: 74%
“…It is generally recognized that surrogates and hNoV survive in a variety of raw, processed, and/or stored foods, including berries, herbs, and molluscan shellfish (Baert et al, 2009;Verhaelen et al, 2012;Richards, 2012;Richards et al, 2012;Poschetto et al, 2007;Butot et al, 2008;Li et al, 2014;Sánchez et al, 2011;Lou et al, 2012). Studies have also shown that the food matrix and environmental factors have a significant impact on virus survival (Le Guyader and Atmar, 2008;Sobsey and Meschke, 2003).…”
Section: Citationmentioning
confidence: 97%
“…However, a major concern is that the results of real-time RT-PCR do not accurately reflect the level of viral infectivity. We previously found that the mechanism of viral inactivation by HPP is the disruption of the viral capsid and not the degradation of genomic RNA, and this capsid disruption would directly affect the receptor binding ability (14,33). Thus, intact virus particles that possess receptor binding activity should be able to bind to PGM-MBs and subsequently be detected by real-time RT-PCR.…”
Section: Discussionmentioning
confidence: 99%